Franco-Romanian contacts and protocol relations (1930-1936) - Nicolescu, Andrei (Technium Social Sciences Journal, 2023)
Romanian-French military relations were enhanced during this period too by many actions and events that referred both to the present and to the most fruitful periods of the collaboration between the two armies. The friendship associations established during the interwar period, both in France and Romania, contributed greatly to the development of relations between the Romanians and the French, between the two armies. During the period 1930-1936 there are also other manifestations of the gratitude of the Romanian authorities towards the French soldiers who contributed to the good relations between the two armies. We can mention an incomplete list, of course, of those who were decorated with orders and medals for such merits. Among those decorated were the names of participants in the 1916-1918 campaign in the French Military Mission in Romania, led by General Berthelot.